Analysis Of Islamic Law And The Book Of Criminal Law In Collection Of Criminal Actions - Samuji; Rusmiyah (El-Faqih : Jurnal Pemikiran dan Hukum Islam, 2022)
In social life, the rules of society are generally governed by a law or regulation that guides action and behavior which is embodied in orders and prohibitions. However, it seems that orders and prohibitions alone are not enough to leave bad deeds, therefore it is necessary to have norms such as religious norms, moral norms, politeness norms, and legal norms. There are four combined theories of committing a crime according to the Criminal Code, namely: first, Stelsel Absorption, Second, Sharpened Stelsel Absorption, Third, Stelsel Cumulation, and fourth Stelsel Cumulation. Whereas Islamic law views that the combination of punishments arises as a result of a combination of committing several criminal acts where one of these actions has not yet received a final decision. Islam recognizes the existence of combined theories of committing criminal acts but these theories are not used absolutely and are limited by the theories of at-tadaahul (inclusion) and al-Jabbu (absorption). Based on the two theories above, in its implementation it is inseparable from the three combined forms of committing a crime, including: a combination of several fingers where all the punishments are pure Allah's rights, a combination of several fingers where in the punishment there are God's rights and adami's or slave's rights, and a combination of several jarimah where the punishment is a pure adami right. Meanwhile regarding the Criminal Code's view of the joint problem of committing a crime, that the provisions regarding this matter have been regulated in articles 63 to 75 of the Criminal Code. In these articles, it has been explained how the system of punishment for someone who has committed a combined crime has been committed.